Fostering resilience among children: a life skills intervention - R. Sreehari; R. Joseph Thomas; A. Radhakrishnan Nair; Balan Rathakrishnan (IAHRW Publications Private Limited, 2013)
The promotion of Child Mental Health can lead to prevention of mental illness. 'Life Skills Education is a proven method for promoting mental health. This indicates that life skills education is required by young people for their holistic development and hence it should be imparted. Well designed, tested and delivered life skills programmes can achieve much in helping children and adolescents become more responsible, healthy and resilient both during childhood and as adults. The concept of resilience emerged in the psychiatric literature in the 1980's, in an attempt to understand individual differences in their responses to stress and adversity, which has a direct linkage with wellbeing. Resilience and Life Skills Training are topics of interests to school psychologists, yet little is known about the relationships among the two. It was hypothesized that resilience would mediate the relationship with Life Skills. The purpose of this study is to investigate the effect of Life Skills Training for fostering Resilience. The training was conducted over a period of 30 days for 60 min per day. A total of 15 students participated in the training programe. Wagnild and Young's Resilience Scale was utilized for assessing the resilience before and after the training programme. The result of the training indicates a positive effect on life skills training for fostering resilience. The statistical analysis also indicates that there is an improvement in the level of resilience on the experimental group.